2009
DOI: 10.1590/s0006-87052009000300002
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento e partição de assimilados em cultivares de arroz diferindo no potencial de produtividade de grãos

Abstract: RESUMOForam estudados o crescimento, a partição de assimilados e a produção de grãos nas cultivares de arroz BRS Pelota (maior produtividade) e BRS Firmeza (menor produtividade). O experimento foi realizado em casa de vegetação, com plantas cultivadas em vaso. Utilizou-se o delineamento experimental inteiramente casualizado, com duas cultivares, nove coletas e quatro repetições por tratamento. Com a cultivar BRS Pelota houve maior acúmulo de matéria seca total (W t ), principalmente no fim do ciclo, bem como m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0
21

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 17 publications
(16 reference statements)
4
19
0
21
Order By: Relevance
“…In plants treated with trinexapac-ethyl, the RGR value was also lower at the physiological maturity stage than at the flowering stage. This downward trend in the relative growth rate as a function of the plant's age is in accordance with the observations of Stone, Portes and Moreira (1988), and Falqueto et al (2009) in rice plants. According to Taiz and Zeiger (2009), RGR reflects the increase in plant dry matter of any organ over a period of time and is a function of the initial size, i.e., of the preexisting material.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…In plants treated with trinexapac-ethyl, the RGR value was also lower at the physiological maturity stage than at the flowering stage. This downward trend in the relative growth rate as a function of the plant's age is in accordance with the observations of Stone, Portes and Moreira (1988), and Falqueto et al (2009) in rice plants. According to Taiz and Zeiger (2009), RGR reflects the increase in plant dry matter of any organ over a period of time and is a function of the initial size, i.e., of the preexisting material.…”
Section: Resultssupporting
confidence: 92%
“…In addition, increased respiratory activity during plant development and self-shadowing can also decrease RGR (URCHEI; RODRIGUES; STONE, 2000), as observed in this experiment. At the end of the plant cycle, RGR is negative due to the death of leaves and buds and to the gradual production of nonassimilatory tissues (MILTHORPE; MOORBY, 1974;FALQUETO et al, 2009), as observed in this trial both with and without growth regulator application (Table 1). Alvarez, Crusciol and Nascente (2012), working with BRS Primavera under field conditions, also observed a steady reduction in RGR with increase in DAE.…”
Section: Resultssupporting
confidence: 56%
See 3 more Smart Citations